1994
DOI: 10.1016/0969-8051(94)90003-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [11C]tetrabenazine as an in vivo radioligand for the vesicular monoamine transporter

Abstract: [11C]Tetrabenazine ([11C]TBZ) is a new in vivo radioligand for positron emission tomographic (PET) imaging of vesicular monoamine transporters. The in vivo distribution, metabolism and pharmacological specificity of [11C]TBZ has been determined in rodents. Regional mouse brain retention of [11C]TBZ is highest in brain regions with greatest monoaminergic innervation (striatum, hypothalamus) and can be reduced with ligands for the monoamine vesicular transporter (TBZ, ketanserin) but not haloperidol, a dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Indirect evidence that the VMAT is involved in psychiatric disorders stems from positron emission tomography (PET) imaging studies. Binding of radiolabled dihydrotetrabenazine, a catecholamine depleter with higher VMAT2 than VMAT1 affinity (DaSilva et al, 1993(DaSilva et al, , 1994 was increased in thalamus and brainstem of BPD patients when compared to controls (Zubieta et al, 2000). Ventral brainstem binding was higher in BPD and SZ patients compared to controls (Zubieta et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…Indirect evidence that the VMAT is involved in psychiatric disorders stems from positron emission tomography (PET) imaging studies. Binding of radiolabled dihydrotetrabenazine, a catecholamine depleter with higher VMAT2 than VMAT1 affinity (DaSilva et al, 1993(DaSilva et al, , 1994 was increased in thalamus and brainstem of BPD patients when compared to controls (Zubieta et al, 2000). Ventral brainstem binding was higher in BPD and SZ patients compared to controls (Zubieta et al, 2001).…”
Section: Introductionmentioning
confidence: 82%
“…In feasibility studies, the biodistribution of [ 11 C]DTBZ in rats was obtained as previously reported by Kilbourn and colleagues (36). The in vivo biodistribution of DTBZ is higher in the pancreas than in many other abdominal organs (Table 1).…”
Section: The In Vivo Biodistribution Of [ 11 C]dtbz Uptake In the Ratmentioning
confidence: 98%
“…Biodistribution studies of [ 11 C]DTBZ in the Sprague-Dawley rats were performed as previously described (36). Briefly, rats were injected via the femoral vein with 150-650 μCi of [ 11 C]DTBZ.…”
Section: Discussionmentioning
confidence: 99%
“…Specific activities of carbon-11-labeled radiotracers were >2000 mCi/μmol at the time of injection. Biodistribution studies of [ 11 C]DTBZ or [ 3 H]DTBZ in Lewis rats were performed as previously described [33]. Briefly, normal rats were injected via the tail vein with 0.5 μCi/g [ 3 H]DTBZ in saline.…”
Section: Chemistrymentioning
confidence: 99%